Transgenic overexpression of the SUR2A-55 splice variant in mouse heart reduces infract size and promotes protective mitochondrial function. Issue 7 (July 2018) - Ramratnam, Mohun; Kenny, Barrett; Kyle, John W.; Wiedmeyer, Brandi; Hacker, Timothy A.; Barefield, David Y.; McNally, Elizabeth M.; Makielski, Jonathan C.
Abstract: ATP-sensitive potassium channels found in both the sarcolemma (sarcKATP ) and mitochondria (mitoKATP ) of cardiomyocytes are important mediators of cardioprotection during ischemic heart disease. Sulfonylurea receptor isoforms (SUR2), encoded by Abcc9, an ATP-binding cassette family member, form regulatory subunits of the sarcKATP channel and are also thought to regulate mitoKATP channel activity. A short-form splice variant of SUR2 (SUR2A-55) was previously shown to target mitochondria and display diaxoxide and ATP insensitive KATP activity when co-expressed with the inward rectifier channels Kir6.2 and Kir6.1. We hypothesized that mice with cardiac specific overexpression of SUR2A-55 would mediate cardioprotection from ischemia by altering mitoKATP properties. Mice overexpressing SUR2A-55 (TG SUR2A-55 ) in cardiomyocytes were generated and showed no significant difference in echocardiographic measured chamber dimension, percent fractional shortening, heart to body weight ratio, or gross histologic features compared to normal mice at 11–14 weeks of age. TG SUR2A-55 had improved hemodynamic functional recovery and smaller infarct size after ischemia reperfusion injury compared to WT mice in an isolated hanging heart model. The mitochondrial membrane potential of TG SUR2A-55 mice was less sensitive to ATP, diazoxide, and Ca 2+ loading. These data suggest that the SUR2A-55 splice variant favorably affects mitochondrial function leading to cardioprotection. These data support a role for the regulation of mitoKATP activity by SUR2A-55.